Benefits of Curcumin in the Vasculature: A Therapeutic Candidate for Vascular Remodeling in Arterial Hypertension and Pulmonary Arterial Hypertension? - Li, Ke-Xue; Wang, Zi-Chao; Machuki, Jeremiah Ong’Achwa; Li, Meng-Zhen; Wu, Yu-Jie; Niu, Ming-Kai; Yu, Kang-Ying; Lu, Qing-Bo; Sun, Hai-Jian (Frontiers in Physiology, 2022)
Growing evidence suggests that hypertension is one of the leading causes of cardiovascular morbidity and mortality since uncontrolled high blood pressure increases the risk of myocardial infarction, aortic dissection, hemorrhagic stroke, and chronic kidney disease. Impaired vascular homeostasis plays a critical role in the development of hypertension-induced vascular remodeling. Abnormal behaviors of vascular cells are not only a pathological hallmark of hypertensive vascular remodeling, but also an important pathological basis for maintaining reduced vascular compliance in hypertension. Targeting vascular remodeling represents a novel therapeutic approach in hypertension and its cardiovascular complications. Phytochemicals are emerging as candidates with therapeutic effects on numerous pathologies, including hypertension. An increasing number of studies have found that curcumin, a polyphenolic compound derived from dietary spice turmeric, holds a broad spectrum of pharmacological actions, such as antiplatelet, anticancer, anti-inflammatory, antioxidant, and antiangiogenic effects. Curcumin has been shown to prevent or treat vascular remodeling in hypertensive rodents by modulating various signaling pathways. In the present review, we attempt to focus on the current findings and molecular mechanisms of curcumin in the treatment of hypertensive vascular remodeling. In particular, adverse and inconsistent effects of curcumin, as well as some favorable pharmacokinetics or pharmacodynamics profiles in arterial hypertension will be discussed. Moreover, the recent progress in the preparation of nano-curcumins and their therapeutic potential in hypertension will be briefly recapped. The future research directions and challenges of curcumin in hypertension-related vascular remodeling are also proposed. It is foreseeable that curcumin is likely to be a therapeutic agent for hypertension and vascular remodeling going forwards.